Pemanfaatan E-Modul pada Perkuliahan yang Menerapkan Project Based Team dan Games Tournament untuk Meningkatkan Kreativitas Mahasiswa pada Mata Kuliah Media Pembelajaran Ekonomi - Rita Syofyan; Rani Sofya; Agus Irianto; Nur Anita Yunikawati; Malina Agustin; Suciyana Febri Adzkia; Nur Fitri Wulandari (Universitas Negeri Padang, 2022)
Graduates of the Economics Education study program are prospective teachers who will face students from the digital native generation. The young generation faced by prospective teachers is a creative and innovative young generation so that students as prospective teachers must also be creative in carrying out learning for their students. Economics and ICT learning media courses are one of the educational subjects that provide provisions for students to be able to carry out creative learning by utilizing technology in learning. The condition of the Covid 19 pandemic which has just ended has made the learning atmosphere return to the new normal with e-learning, face-to-face and hybrid. In the subject of economics and ICT learning media, the final result is that students are expected to be able to produce creative and innovative learning media that are attractive to students. However, the problem faced is the lack of student creativity in producing interesting learning media for their students. Efforts to be made by lecturers are to use e-modules in learning Economics and ICT Learning Media which implement team based projects and game tournaments in order to increase student creativity. This research is a classroom action research conducted in the Economics and ICT Learning Media class Section 202210530013 with a total of 18 students. This PTK research was carried out to increase student creativity, at least 70% of students increased their creativity from the results of the initial assessment. This research was carried out in several cycles to achieve the expected results.